Applicability of a “Multi-Stage Pulse Labeling” 15N Approach to Phenotype N Dynamics in Maize Plant Components during the Growing Season - de Oliveira Silva, Amanda; Camberato, James J.; Coram, Tristan; Filley, Timothy; Vyn, Tony J. (Frontiers in Plant Science, 2017)
Research using labeled isotopic N (15N) can precisely quantify fertilizer nitrogen (N) uptake and organ-specific N allocation from field crops such as maize (Zea mays L.). The overall research objective was to study plant N uptake patterns potentially correlated with N use efficiency (NUE) in field-grown maize hybrids using a “multi-stage pulse labeling” 15N phenotyping strategy with an emphasis on the reproductive period. Five hybrids varying in NUE were compared under zero N fertilizer application (0N) plus a moderate rate of 112 kg N ha-1 (112N) in 2013 (2 locations) and 2014 growing seasons. The equivalent of 3.2 (2013) to 2.1 (2014) kg of 15N ha-1, as labeled Ca(15NO3)2, was injected into soil on both sides of consecutive plants at multiple stages between V14 and R5. Aboveground plant biomass was primarily collected in short-term intervals (4 to 6 days after each 15N application) in both years, and following a single long-term interval (at R6 after 15N injection at R1) in 2014. Averaged across hybrids and site-years, the moderate N rate (112N) increased absolute 15N uptake at all stages; however, plants in the 0N treatment allocated proportionally more 15N to reproductive organs. Before flowering, short-term recovery of 15N (15Nrec) totaled ~0.30 or 0.40 kg kg-1 of the 15N applied, and approximately 50% of that accumulated 15Nu was found in leaves and 40% in stems. After flowering, plant 15Nrec totaled approximately 0.30 kg kg-1 of 15N applied, and an average 30% of accumulated 15Nu was present in leaves, 17% in stems, and the remainder - usually the majority - in ears. At the R5 stage, despite a declining overall rate of 15N uptake per GDD, plant 15Nrec represented ~0.25 kg kg-1 of 15N applied, of which ~65% was allocated to kernels. Overall long-term 15Nrec during grain filling was ~0.45 and 0.70 kg kg-1 of total 15N applied at R1 with 0 and 112N, respectively, and most (~77%) 15N uptake was found in kernels. The “multi-stage pulse labeling” technique proved to be a robust phenotyping strategy to differentiate reproductive-stage N uptake/allocation patterns to plant organs and maize efficiencies with newly available fertilizer N.